Evaluation of natural fibre composites using analytical hierarchy process - Arep @ Ariff, Hambali; Salit, Mohd Sapuan; Ismail, Napsiah; Yusoff, Nukman (2009)
There is an increased in the use of natural fibre composites in automotive industry in recent years. The increasing interest in these materials owing to various benefits to the automakers can be obtained. However, to determine the right selection of natural fibres composite to be used in manufacturing of automotive components is very crucial. Inappropriate selections can be disastrous from both performance and economic perspectives. To solve this problem, analytical hierarchy process (AHP) is one of multi-attribute decision making tools, was implemented. To illustrate the use of analytical hierarchy process, 5 different types of natural fibre polymer composites were considered. It is showed that analytical hierarchy process approach assists designers to effectively evaluate various natural fibre polymer composites. Thus, the paper discussed the potential of using analytical hierarchy process in solving and determining the most appropriate natural fibre polymer composites to be used in manufacturing of automotive components.